The Use of Schematic-activation Strategy in Teaching Young EFL Learners Reading Comprehension - Etika Ariyani (Linguistics and ELT Journal, 2018)
Reading is one of the important skills that the students have to master. However, many students have difficulties in comprehending the reading text. To solve this condition, the researcher used schema activation strategy to help students understand reading comprehension. The purpose of this research was to investigate whether the use of schema activation strategy is effective or not in teaching reading comprehension at the second-grade students of MTs Tarbiyatul Mustafid in academic year 2017/2018. This study was quasi-experimental design using two classes were VIII B class was taken as an experimental class, and VII-A was taken as control class. The population of this research involved 60 students from the second grade in MTs Tarbiyatul Mustafid Batu Simpang. By using purposive sampling, the researcher took the students as a sample. In collecting the data, this study used pre-test, treatment, and post-test as the data collection procedure then followed by analyzing the data by using the t-test formula. Then the result of statistical analysis of t-test in this research was 2.85. It was higher than critical values for t- table in the degree of freedom (df) of 58 is 2.021(0.05%) and 2.704(0.01%). The researcher concludes that mean score before and after teaching by using schema activation strategy has a difference. It means the alternative hypothesis (ha) was accepted. The use of schema activation strategy in teaching reading comprehension at the second-grade students of MTs Tarbiyatul Mustafid Batu Rimpang is effective.